Governed for God's praise - Robinson, David (Country Life, 2022)
The Abbey of St Mary and St Nicholas at Beeleigh was founded towards the end of the 12th century for a community of Premon-stratensian canons, named after the mother house of their order, Premontre (Aisne), in north-eastern France. With the support of Robert Mantell (d. 1190), lord of Little Marlow and sheriff of Essex, the canons were settled on the river Chelmer, a short distance upstream from the market town of Maldon. [...]in 1249, William de Fancourt and his wife, Rose, granted the canons a plot of land, in return for which during certain Masses-they were to light a candle 'before the heart of St Roger for ever'. Two of the ground-floor spaces are perfect embodiments of comparatively restrained early 13th-century architecture, namely the chapterhouse and the day room.
Place: Bath Publisher: Future Publishing Ltd
Keywords: beeleigh

Beeleigh Abbey: A Guide and History - Foyle, Christopher (Christopher Foyle Publishing, 2012)
Keywords: beeleigh

A Short History of Beeleigh Abbey (W. and G. Foyle Ltd., 1950)
Keywords: beeleigh

Beeleigh Abbey, Essex - Fowler, Robert Copp; Clapham, Alfred William (R.E. Thomas, 1924)
OCLC: 977233344
Keywords: beeleigh

A Play of Beeleigh Abbey (The Times, 1921)
Keywords: beeleigh

Dissolution 1536-7: suffered by Brother Ambrose, of Beeleigh Abbey, temp. Henry VIII. - Grantham, A. E. (The Eastern Press, 1917)
Keywords: beeleigh

Buried Treasure at Beeleigh Abbey - Clark, A. (Essex Review: An Illustrated Quarterly Record of Everything, 1907)
Keywords: beeleigh

House of Premonstratensian Canons: Abbey of Beeleigh by Maldon - Page, William; Round, J.H. (A History of the County of Essex, 1907)
Keywords: beeleigh

Historical account of Beeleigh Abbey, Essex - Draper, George (G. Draper, 1818)
Keywords: beeleigh